Internalization Of Multicultural Values In Learning Pancasila And Citizenship Education - Thomy Sastra Atmaja (Sean Institute, 2024)
This research discusses strategies, challenges and solutions in implementing multicultural education in learning Pancasila and Civic Education in Indonesia. These challenges include limited resources and institutional support, which can be overcome through cooperation with higher education institutions, NGOs, and international organizations, as well as the development of networks between PPKN teachers. Support from schools, governments, and communities is also needed to support multicultural education. The purpose of this study is to explore effective strategies in internalizing multicultural values in PPKN learning. The results showed that internalization of multicultural values in PPKN learning is important to maintain national identity and diversity values. Through a multicultural approach, students are expected to understand, appreciate differences, and develop inclusive attitudes and cooperation. Participatory and interactive strategies, such as the use of storytelling methods and habituation of behavior, are necessary in the integration of multicultural values. Support from various parties, the use of diverse media and learning resources, and curriculum development that focuses on multicultural themes are key in internalizing multicultural values. Challenges such as resistance from students or communities that are less open to diversity can be overcome through inclusive, empathetic, and engaging learning methods.